(untitled) (The Journal of Theoretical Accounting Research, 2026)
Goodwill has travelled a long conceptual and regulatory journey—from a loosely understood commercial custom in nineteenth-century legal practice to a highly codified but still controversial element of contemporary financial reporting. The movement from cost-based amortization regimes to the impairment-only model under IFRS 3 is not merely a technical change in measurement; it reflects deeper philosophical negotiations about what financial statements are meant to do, whom they are designed to serve, and how uncertain future-oriented benefits should be represented. This paper examines the historical evolution of goodwill accounting, the theoretical paradigms that underpin competing treatments, the practical consequences of the current impairment-only regime and the technological impact. Drawing on historical analysis, interpretive reading of standards, and conceptual synthesis, the paper argues that goodwill accounting embodies a persistent tension between stewardship-oriented prudence and neo liberal valuation logic grounded in investor decision-usefulness. Neither pure amortization nor pure impairment adequately resolves this tension. The paper therefore proposes an emerging hybrid paradigm that combines disciplined amortization with trigger-based impairment, supported by enhanced technological disclosure and governance oversight. This hybrid model is presented as a more conceptually coherent, ethically defensible, and decision-useful way of representing goodwill.